Management practices and productivity status of cattle and buffaloes in Rajasthan - GUPTA, D C; A, SURESH; MANN, J S (The Indian Journal of Animal Sciences, 2011)
Livestock sector is an important source of livelihood in Rajasthan for rural masses and generates regular income to the farmer. Bovine farming is a process to convert available feed and fodder material (input) into milk and other byproducts (output). The present study assesses the management practices of cattle and buffalo in Rajasthan. Detailed information collected from farmers of all the nine agro-climatic sub-zones of Rajasthan were used for the study. The data were collected on various management practices including economic traits. Majority of farmers were relying on natural service for breeding their bovines. Adoption of AI was poor possibly due to poor awareness among the farmers or due to lack of confidence in AI or lack of accessibility to the facilities. Mid-heat detection and pregnancy diagnosis test were conducted by most of the farmers. Majority of farmers fed chaffed green and dry fodder roughages at stall. Lactating animals were offered concentrate and mineral mixture/common salt on individual basis. Majority of farmers washed the udders before milking the animals. Most of the farmers housed the animals in pens having pucca stall with kachcha floor. The average per day milk yield, peak milk yield and age at first calving were found significantly associated with each other and varied with the change in agro-climatic zones.